An ATCA survey of Sagittarius B2 at 7 mm: Chemical complexity meets broad-band interferometry - Corby, J.; Jones, P.; Cunningham, M.; Menten, K.; Belloche, A.; Schwab, F.; Walsh, Andrew; Balnozan, E.; Bronfman, L.; Lo, N.; Remijan, A. (Oxford University Press, 2015)
© 2015 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society. We present a 30-50 GHz survey of Sagittarius B2(N) conducted with the Australia Telescope Compact Array with ~5-10 arcsec resolution. This work releases the survey data and demonstrates the utility of scripts that perform automated spectral line fitting on broad-band line data. We describe the line-fitting procedure, evaluate the performance of the method, and provide access to all data and scripts. The scripts are used to characterize the spectra at the positions of three HII regions, each with recombination line emission and molecular line absorption. Towards the most line-dense of the three regions characterized in this work, we detect ~500 spectral line components of which ~90 per cent are confidently assigned to H and He recombination lines and to 53 molecular species and their isotopologues. The data reveal extremely sub-thermally excited molecular gas absorbing against the continuum background at two primary velocity components. Based on the line radiation over the full spectra, the molecular abundances and line excitation in the absorbing components appear to vary substantially towards the different positions, possibly indicating that the two gas clouds are located proximate to the star-forming cores instead of within the envelope of Sgr B2. Furthermore, the spatial distributions of species including CS, OCS, SiO, and HNCO indicate that the absorbing gas components likely have high UV-flux. Finally, the data contain line-of-sight absorption by ~15 molecules observed in translucent gas in the Galactic Centre, bar, and intervening spiral arm clouds, revealing the complex chemistry and clumpy structure of this gas. Formamide (NH2CHO) is detected for the first time in a translucent cloud.